Integrating Mobile and Portable Technologies With In-Person and Telehealth Care to Increase Perinatal Healthcare Equity for the Unstably Housed. Issue 1 (January 2023) - Michel, Alexandra; Minton, Lea; Sullivan, Cathlyn; Fontenot, Holly; Lee, Men-Jean
Abstract : Pregnant people living in rural areas are at an increased risk of experiencing poor perinatal outcomes due, in part, to the need to travel long distances to see a perinatal care provider. Telehealth care has been used successfully to increase access to perinatal care but requires patients to have access to broadband Internet access and devices capable of establishing secure connections so they can participate in their care. This places an additional burden on unstably housed pregnant persons who may not have access to the required technology. The Midwifery Integrated Home Visitation Program was developed to bridge this digital divide by bringing perinatal care services to the unstably housed at their desired location of care. The included case studies outline how telehealth and portable technology were used to address the medical and nonmedical needs of unstably housed pregnant people. They also outline how bridging the digital divide by combining in-person perinatal care with mobile technology, portable technology, and telehealth care has the potential to decrease unnecessary emergency department care and ambulance use while facilitating the receipt of appropriate care and thus potentially preventing poor perinatal outcomes.